Graduate Attributes and Legal Skills: Integration or Disintegration? - Sharon Christensen; Sally Kift (Legal Education Review)
Griffith University introduced an integrated Law and Environmental Science degree in 1992. Students who successfully complete the five-year course receive both a Bachelor of Law and a Bachelor of Science degree. The first graduates entered the work force in 1997. With burgeoning regulation of the environment these graduates will help fill a growing demand for legally qualified environmental scientists or scientifically qualified lawyers. The first years of the degrees of the course are devoted to studying the two discipline areas, with integration across disciplines wherever possible. One example is that many of the core legal subjects set an integrated law and environmental science assignment that, for instance, might include the environmental and legal aspects of toxic torts. The theoretical and philosophical frameworks of law and environmental science are integrated in the fourth year subject, Jurisprudential Theories of Law and the Environment. This subject, together with a final year integrated research project, represents a culmination of the interdisciplinary study across the two degrees. The subject is a novel one, being the first of its kind in Australia, and is the focus of this article. We outline the aims of the subject, its approach, content, teaching and assessment methods, summarise innovative student achievements, and provide illustrative feedback from students.